Saul Bellow : vision and revision - Fuch, Daniel, 1934- (New Delhi : Affiliated East-West Press, 1992)
In the first critical study to deal with all of Bellow's fictional works to date, Fuchs gives a unique look at the novelist's imagination at work. Granted sole permission to quote from all of Bellow's unpublished manuscripts and letters, Fuchs studies the stages of Bellow's work, the stages that altered the essential nature of characters and scenes. Analyzing Bellow's literary and cultural milieus, he elucidates his complete vision and shows how this vision manifested itself in revisions. Providing critical readings of individual works, such as Augie March, Herzog and Humboldt's Gift, Fuchs presents critical insights into how the works were composed and how they evolved through numerous drafts. ISBN 81-85336-87-3 (For sale in India under the Indo-American Cooperative Publishing Program at Rs.80.00).
Includes bibliographical references and index.
Keywords: Bellow, Saul -- Criticism, Textual; Bellow, Saul; Criticism, interpretation, etc